Out of Time: Maternal time and disability - Robertson, Rachel (University of London Birkbeck College, Department of Psychosocial Studies, 2015)
Starting from a maternal experience of temporal dissonance, this article takes a feminist disability studies approach to exploring disabled maternal temporality. After establishing how notions of time are central to discourses about disability and summarising some key discussions on women's time and caring, I use Lisa Baraitser's work on interrupted time and mothering to develop a parallel between the way both maternal and disabled subjectivities problematise temporality. My discussion then draws on Alison Kafer's and Rosemarie Garland-Thomson's discussions about futurity to explore the relationship between futurity, maternal subjectivity and disability, arguing for the ethical value of the maternal experience.